Encycylopedia of sport and games - Goesl, R.G; Goel, Gaurav (Delhi : Vikas Publishing, 2007)
This title provides the rules and regulations governing sports and games with brief historical backgrounds for each. Specific know-how about organising tournaments and championships is provided along with details of infrastructural requirements. This ed. originally published: 1995
Includes Bibliographical reference and index.
Keywords: Encyclopedia. -- dictionary; Sport and games